Pelaporan Kinerja Holistis Program Kampung Nelayan Maju di Kelurahan Oesapa Melalui Dinas Perikanan Kota Kupang untuk Berkontribusi terhadap Blue Economy - Natasya Pintauli Hendrikas Manu; Moni Wehelmina Muskanan; Indah Mutiara (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The Kampung Nelayan Maju (Kalaju) Program is an initiative by Indonesia’s Ministry of Marine Affairs and Fisheries (KKP) to enhance the productivity of coastal communities through sustainable village development. This study holistically examines the Kalaju program cycle in Oesapa Subdistrict, Kupang City, encompassing the planning, implementation, performance measurement (accounting), and reporting stages, applying the Sustainability Accounting and Reporting (SAR) Framework developed by Schaltegger and Wagner (2006). Using a qualitative case study and content analysis approach, data were collected through in-depth interviews and documentation from key stakeholders. The findings reveal that while the involvement of the Department of Fisheries, local government, and community groups (Pokmas) is evident, the reporting system is not yet optimal to comprehensively capture the program’s social, economic, and environmental impacts. Reporting remains largely output-based and lacks integration with outcome-oriented indicators. Therefore, it is highly recommended to integrate the SAR Framework into the technical design of the program at the national level, thereby embedding sustainability principles and enhancing the accountability and effectiveness of regional stakeholders in implementing and reporting program outcomes.